Pengaruh Permainan Target Simpai terhadap Peningkatan Kemampuan Free Throw pada Peserta Ekstrakurikuler Bola Basket Kelas X : (SMA Negeri 1 Subang) - Gempar Al-Hadist; Arif Fajar Prasetiyo; Raisya Nur Amelia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of the hoop target game on improving free throw skills among extracurricular basketball participants of grade X at SMA Negeri 1 Subang. The background of this research is based on the importance of free throw ability as one of the fundamental techniques that significantly influence success in basketball games, while many students still experience difficulties in achieving shooting accuracy. The research method employed was an experimental approach with a One Group Pretest-Posttest Design. The study population consisted of all 15 students participating in the basketball extracurricular program, who were also used as the research sample through a total sampling technique. The instrument used to collect data was a free throw shooting test. The validity test produced a coefficient of 0.860 and reliability of 0.750, indicating that the instrument was feasible to use. Data analysis was carried out using descriptive statistics and significance testing. The pretest results showed a minimum score of 1, maximum of 5, mean of 3.00, and a standard deviation of 1.195. Meanwhile, the posttest results indicated a minimum score of 3, maximum of 8, mean of 4.933, and a standard deviation of 1.222. The hypothesis test produced a significance value of p = 0.000 < 0.05, confirming that the hoop target training method had a significant effect on improving free throw ability. Thus, it can be concluded that the application of the hoop target game as a training method is effective in enhancing the free throw skills of basketball extracurricular participants at SMA Negeri 1 Subang. This research is expected to serve as a reference for physical education teachers and coaches in developing more varied and effective training methods to improve basic basketball skills.